Habitar la imagen : el concepto de utopía y realidad en la obra de Sofía Jack - Coello, Yolanda Ríos (2017)
The article is focused on the concept of Utopia and reality on Sofía Jack’s work. Two key projects are analyzed: the “Casa B-300” and “Todo lo sólido se desvanece en el aire” where the artist demonstrates her concerns about the living space and by its image portrayed during the Modern Movement